The Development of a Vocational Rehabilitation Program to Assist Individuals With MDRTB and TB in Returning to Work - Mogammad Shaheed Soeker; Ayesha Jainodien (Occupational Therapy International)
Conclusion: The study provided a description of the components of a vocational rehabilitation program that has been adapted from the Model of Occupational Self-Efficacy (MOOSE). The above program has been designed for individuals diagnosed with PTB/MDRTB and has the potential to assist them in returning to work. It is suggested that vocational rehabilitation programs be incorporated into general medical programs that focus on improving the functioning of individuals diagnosed with PTB/MDRTB.